La estética contemporánea de la violencia de género: una mirada desde el siglo XXI (Contextos) - Diego Mauricio, Higuera Jiménez (Corporación Universitaria Americana, 2022)
Violence - as distinct from power - always seeks instruments for its existence. for its existence. Hobbes' old phrase is interesting to guide our to guide our reflections in the contemporary world: "Covenants without coercive coercive measures, they are nothing but words". After the Second World War World War II was not followed by a period of peace, but by the Cold War and the establishment of a military-military complex. and the establishment of a military-industrial complex (Arendt, 1970). Karl Marx (2010) in the 18th Brumaire of Louis Bonaparte stated that historical events happen twice in the course of history. historical events take place twice in history: once as a tragedy and the tragedy and the second as farce. It is precisely on this second phase or repetition of historical events that this book is about. The The idea of trying to make an approach to reality studies of the 21st century with respect to the aesthetics of violence, understanding this aesthetics as the presentation of this particular as the presentation of this particular violence of contemporaneity, with its facilitating instruments, its with its facilitating instruments, with its discourses and its practices that make possible the naturalization of a policy that castrates rights. Does this aesthetics of violence in our contemporaneity behave in a similar way to the aesthetics of historical processes? similar to the aesthetics of previous historical processes? Bastide (2006) when analyzing aesthetics, argues that society shapes the reaction to it, and from the reaction to it, and in the same way here society shapes the practices of violence, especially practices of violence, especially when we analyze violence and its relation to gender issues. and its relationship to gender issues.